Pre-historic Failure in Relation to Recent Slope Stability: A Case Study at km 71.83 East-West Highway, Gerik, Malaysia - Abd Kadir, Askury (2009)
Abstract - A 40m slope, striking to ENE-WSW shows a creeping phenomenon, where the tensional cracks are observed everywhere on the slope face. It is in the unstable condition of the rock masses, showing very loose material and easy to fall off even with a small scale excavation or removal of material. The chaotic rock masses condition with the mixture of rocks and soils indicate the slope has previously failed by the rotational slide, and keeps moving as creep. This slope is underlain by the Ordovician-Silurian quartz-mica schist intruded by the Triassic microdiorite. The rock masses are generally brittle with four sets of prominent joints, and sometimes are exhibited fault plane shown by slickensided surfaces. The structural analysis uses stereographic projection to identify the possible failure mode on the rock slope, and obtained a toppling failure to the North. The rock mass was quantitatively rated within Class III-IV (poor to very poor rock) with the cohesion strength 100-200kPa and friction angle at 15-25o based on RMR classification. It presumed that the slope condition is at tensional mode with residual shear strength. Therefore, a detail geological investigation needs to be performed to identify the geological history of the area for cost effectiveness on slope protection and mitigation measures.